ANALISIS PRILAKU DISIPLIN BELAJAR SISWA MTs DARUL AROFAH - Endang Erawati Endang Erawati; Roswamati '; Tri Umari Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack : This study, entitled "Analysis of Behavior Discipline Student MTs Darul Arofah" conducted from July 2014 to September 2014. From the symptoms seen in students of MTs Darul Arofah Tanjung Medan problems identified in this study are: 1) the presence of students who violate color uniform predetermined day. 2) the presence of students who enter school late because of utilizing transportation used. 3) students who smoke in the backyard of the school at a certain hour, stealing the results of plantation residents in hours of study by reason of urination, and fight at rest. The objectives of this study were: 1) to describe the behavior of the student's learning discipline dar Arofah MTs. 2) to describe the percentage of students learning the discipline of MTs Darul Arofah.In this study, the author uses descriptive research method. The population in this study were students of class IX MTs Darul Arofah Tanjung Medan Pujud TA. 2013/2014 with a total of 65 students consisting of as many as 33 students a class IXA and IXB class of 32 students by using total sampling technique. Based on the research and data processing results can be concluded as follows: 1) Discipline students of class IX MTs Darul Arofah Pujud TA.2013 / 2014 self-disciplined child indicators based on religious values most students never read prayers when starting any activity. 2) Discipline students of class IX MTs Darul Arofah Pujud TA.2013 / 2014 on indicators of children who disciplined themselves based on cultural values most students always use a uniform that does not comply with the rules of the school. 3) Discipline students of class IX MTs Darul Arofah Pujud TA.2013 / 2014 self-disciplined child indicators based on association rules most students happy to join with drug users. 4) Discipline students of class IX MTs Darul Arofah Pujud TA.2013/2014 self-disciplined child indicators based on children who have attitudes that are meaningful to her child, the community, the nation and the country most students always follow friends who pull at the time hours of study. 5) Discipline Thus students of class IX MTs Darul Arofah Pujud TA.2013/2014 can be considered good. Keywords: Behavioral, learning discipline student